WARFARIN: PLACE IN THE ANTICOAGULANT THERAPY TODAY - N. A. Novikova; A. N. Volovchenko («REMEDIUM GROUP» Ltd., 2016)
A trial fibrillation is the most common cardiac source of systemic emboli and car-a significant reduction or even blockage of dioembolic stroke. Anticoagulants are recommended for preventing  stroke in patients with non-valvular  atrial fibrillation. Warfarin reduces the risk of stroke in patients with AF by approximately two-thirds. New oral anticoagulants are becoming more common in recent years. Despite this, a number of clinical situations remain where the only possible anticoagulant is warfarin.